Enteric methane emissions from dairy and beef cattle: a meta-analysis - Wang, Junqin (Kansas State University, 2014)
This study reviewed state-of-the-art cattle enteric methane (CH4) emissions with three reported measuring units: g/head/d, g/kg DMI (dry matter intake), and %GEI (gross energy intake). Cattle emissions studies included in this meta-analysis were reported from 1995 to 2013. Fifty-five published studies were analyzed with specific objectives: (1) to gain basic information regarding magnitudes and distributions of enteric CH4 emission rates with various units, regions, cattle types and feed situations; (2) to identify and evaluate effects of influence factors or diet mitigation techniques on enteric CH4 emissions; and (3) to evaluate Intergovernmental Panel on Climate Change (IPCC) approaches to estimate enteric CH4 emissions. Emissions data (n=165) with the unit of g/head/d had large variances and non-normal distribution, and were not homogeneous across the studies. Emissions data (n=134) with the unit of g/kg DMI were not homogeneous across the studies, while emissions data (n=76) with the unit of %GEI had small variances and normal distribution, and were homogeneous across the studies. Therefore, data with the unit of %GEI may be better for meta-analysis compared to data with the units of g/head/d and g/kg DMI; however, the number of data with the unit of %GEI was small relative to the number of data with the units of g/head/d and g/kg DMI. Enteric CH4 emissions with the unit of g/head/d are significantly influenced by geographic region, cattle classification, sub-classification, humidity, temperature, body weight, and feed intake. Emissions and feed intake had a strong positive linear relationship with R2 of 0.75 (n=148). Emissions with the unit of g/kg DMI are significantly affected by humidity, body weight, and feed intake. The relationship between emissions and feed intake is positive. Emissions with the unit of %GEI are significantly associated with humidity, production stage, and body weight. IPCC Tier 1 and Tier 2 estimated emissions were approximate to most of the measured enteric CH4 emissions; however, the residuals were not normally distributed. Based on results from PRD method and paired t-tests, IPCC Tier 1 overestimated emissions in Asian studies, underestimated emissions in European studies for beef cattle, and underestimated emissions in Oceanian studies for dairy cattle. IPCC Tier 2 underestimated emissions in Asian studies for beef cattle. The underestimated emissions of IPCC Tier 2 in Asian studies might result from no consideration of effects from production stage and body weight.
Keywords: Enteric CH4 emission; Cattle; GHGs; Environmental Engineering (0775)